1994
DOI: 10.1017/s0952523800003096
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemical signatures revealed by glutamine labeling in the chicken retina

Abstract: Postembedding immunocytochemistry was used to determine the retinal distribution of the amino acid glutamine, and characterize amino acid signatures in the avian retinal ganglion cell layer. Glutamine is a potential precursor of glutamate and some glutamatergic neurons may use this amino acid to sustain production of glutamate for neurotransmission. Ganglion cells, cells in the inner nuclear layer, and some photoreceptors exhibited glutamine immunoreactivity of varying intensity. Ganglion cells demonstrated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0
1

Year Published

1995
1995
2002
2002

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 67 publications
4
27
0
1
Order By: Relevance
“…The molecular phenotypes of ganglion cells distinguish them from all other retinal neurons (Sherry and Ulshafer, 1992;Kalloniatis et al, 1994Kalloniatis et al, , 1996Marc et al, 1995Marc et al, , 1998. Classification shows that EDQ and EDQ␥ cells are large ganglion cells, although no biological reason for this specialization is obvious.…”
Section: Metabolic Signaturesmentioning
confidence: 99%
“…The molecular phenotypes of ganglion cells distinguish them from all other retinal neurons (Sherry and Ulshafer, 1992;Kalloniatis et al, 1994Kalloniatis et al, , 1996Marc et al, 1995Marc et al, , 1998. Classification shows that EDQ and EDQ␥ cells are large ganglion cells, although no biological reason for this specialization is obvious.…”
Section: Metabolic Signaturesmentioning
confidence: 99%
“…For example, certain regulatory proteins are differentially partitioned within subsets of retinal neurons that apparently use the same amino acid neurotransmitter (e.g., Pasteels et al, 1990;Wgssle et al, 1994). Limited analyses of amino acid coexistence have also revealed varied combinations in retinal and central neurons Zhang et al, 1991;Crooks and Kolb, 1992;Kritzer et al, 1992;Martin and Gtinert, 1992;Kalloniatis et al, 1994;Marc, 1994). In this report, we explore amino acid content in retina using (1) a set of 10 anti-amino acid IgGs as probes of intracellular amino acid levels and (2) pattern recognition methods.…”
Section: Pattern Recognitionmentioning
confidence: 99%
“…Both bipolar cells and ganglion cells appear to be glutamatergic, but previous work has suggested that ganglion cells possess amino acid immunoreactivities that differ measurably from bipolar cells (Kalloniatis et al, 1994). Pattern classification of the proximal inner plexiform layer (YET + rgb mapping, Fig.…”
Section: Pattern Recognitionmentioning
confidence: 99%
“…The eyes were then dissected through the optic nerve such that samples containing the entire width of the retina were dehydrated and embedded in Medcast resin (Pelco, Redding, CA) without postosmication. Tissue sections of 350-nm-thickness were cut on an ultramicrotome (Reichert-Jung Ultracut S), placed on Teflon-coated 18-well slides (Cel-line, Newfield, NJ) and processed for postembedding immunocytochemistry (Kalloniatis and Fletcher, 1993;Kalloniatis et al, 1994Marc et al, 1995).…”
Section: Immunocytochemistrymentioning
confidence: 99%
“…Silver intensification was used to visualise the secondary antibody Kalloniatis and Fletcher, 1993). The specificity of the antibodies has been previously described (Marc et al, , 1995Kalloniatis and Fletcher, 1993;Kalloniatis et al, 1994Kalloniatis and Napper, 1996;Fletcher and Kalloniatis, 1996a,b).…”
Section: Immunocytochemistrymentioning
confidence: 99%